FACTORS AND LEGAL FOUNDATIONS FOR THE DEVELOPMENT OF “GREEN ECONOMY” IN UZBEKISTAN - Zokhidov Ulugbek Shokirjon ugli (Ecominds Press, 2025)
This article discusses the factors and legal foundations for the development of the “green economy” in Uzbekistan, the essence of the United Nations “Sustainable Development” concept, the deepening of structural changes in Uzbekistan, and its objectives. Particular attention is given to the formation of a “green” economy, as well as the stimulation of “green” growth and development.
Keywords: Sustainable development, “green” economy, “green” growth, new development model, sustainable development goals.